2016
DOI: 10.18632/oncotarget.12216
|View full text |Cite
|
Sign up to set email alerts
|

The human nucleophosmin 1 mutation A inhibits myeloid differentiation of leukemia cells by modulating miR-10b

Abstract: Mutations in the nucleophosmin 1 (NPM1) gene are the most frequent genetic alteration in acute myeloid leukemia (AML). Here, we showed that enforced expression of NPM1 mutation type A (NPM1-mA) inhibits myeloid differentiation of leukemia cells, whereas knockdown of NPM1-mA has the opposite effect. Our analyses of normal karyotype AML samples from The Cancer Genome Atlas (TCGA) dataset revealed that miR-10b is commonly overexpressed in NPM1-mutated AMLs. We also found high expression of miR-10b in primary NPM1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Our group and others found that KLF4 gene expression is silenced by promoter hypermethylation in B‐cell lymphomas and T‐ALL . In addition to CpG methylation, downregulation of KLF4 is associated with deregulation of microRNAs such as miR‐10a and miR‐10b, and the transcriptional repression of KLF4 by CDX2 in AML is associated with inhibition of PPARγ signaling . Conversely, when human CD34 + cells are transduced with ZMYM2‐FGFR, the fusion protein product of the t(8;13)(p11;q12) chromosomal translocation found in myeloproliferative neoplasm, and transplanted into NSG mice, the mice display elevated KLF4, suggesting a potential oncogenic function .…”
Section: Role Of Klf4 In Leukemic Stem Cellsmentioning
confidence: 93%
“…Our group and others found that KLF4 gene expression is silenced by promoter hypermethylation in B‐cell lymphomas and T‐ALL . In addition to CpG methylation, downregulation of KLF4 is associated with deregulation of microRNAs such as miR‐10a and miR‐10b, and the transcriptional repression of KLF4 by CDX2 in AML is associated with inhibition of PPARγ signaling . Conversely, when human CD34 + cells are transduced with ZMYM2‐FGFR, the fusion protein product of the t(8;13)(p11;q12) chromosomal translocation found in myeloproliferative neoplasm, and transplanted into NSG mice, the mice display elevated KLF4, suggesting a potential oncogenic function .…”
Section: Role Of Klf4 In Leukemic Stem Cellsmentioning
confidence: 93%
“…NPM1 is a multifunctional protein that controls cell growth and genome stability through a mechanism either involving nucleolar-cytoplasmic shuttling or a fine modulation of the whole BER pathway 11,19 . Recently, an important role for NPM1 in miRNA biology, associated with cancer development, was outlined [20][21][22] . Abnormal cytoplasmic APE1 and NPM1 levels were associated with the oncogenic progression and chemoresistance of HGSC (high-grade serous ovarian adenocarcinoma), a prediction of a poor prognosis therein 23,24 , and a dysregulation of the BER and miR-221/222 processing pathways in AML cells 18,25 .…”
mentioning
confidence: 99%
“…miR-10b has been widely studied in cancer (29,30), angiogenesis (31) and embryonic development (32) by focusing on different targets. It has been found that miR-10b regulates myeloid differentiation and neuroblastoma cell differentiation (24,25). Okamoto et al found that miR-10b was significantly downregulated during osteoblast differentiation (26).…”
Section: Discussionmentioning
confidence: 99%
“…miR-10b has been suggested as a regulator for cell differentiation (24,25). A recent study has reported that miR-10b shows decreased expression during osteoblast differentiation (26).…”
Section: Introductionmentioning
confidence: 99%